EFFECTS OF FINANCIAL PERFORMANCE ON ESG PERFORMANCE: EVIDENCE FROM INDONESIAN SHARIA COMPANIES - Koh, Heskey; Ervina Waty; Said, Jamaliah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2025)
This study analyzes the correlation between financial performance and Environmental, Social, and Governance (ESG) performance in Indonesian Shariah-compliant companies, leading to a significant research gap in the context of Islamic finance. This study employs panel data from 20 companies listed on the Jakarta Islamic Index (JII) from 2019 to 2023, comprising 100 observations. A multiple linear regression analysis is conducted to investigate the relationships between ESG scores and financial indicators such as Return on Equity (ROE), total assets, and Tobin's Q. The regression model indicates statistically significant findings, with ROE showing a significant positive correlation with ESG performance. Specifically, a 1 percentage point increase in ROE is associated with a 0.245 point increase in the ESG score, which supports a model where financial performance facilitates sustainability. Company size and market valuation do not exhibit significant relationships with ESG factors. Findings suggest prioritizing companies with robust ROE performance as indicators of financial health and ESG leadership within Shariah-compliant firms. This study presents initial empirical evidence regarding the relationship between financial performance and ESG factors within the Indonesian Islamic capital market. It challenges conventional assumptions about the causality between ESG and performance by showing that profitability facilitates sustainability performance in Islamic firms. This study provides significant insights into the expanding global Islamic finance sector, anticipated to attain USD 7.5 trillion by 2028, while advocating for integrated Islamic ESG frameworks that acknowledge financial performance as a basis for effective sustainability implementation.